Review and Improvement of Runway Friction and Aircraft Skid Resistance Regulation, Assessment and Management - Gadel Baimukhametov; Greg White (Applied Sciences)
Runway skid resistance is crucial for the safety of aircrafts. Despite being internationally regulated, investigation reports published by the Australian Transport Safety Bureau and the US National Transportation Safety Board indicate that 4.9–22% of runway excursion accidents are related to insufficient friction, or to friction overestimation. Consequently, based on this review of friction physics, aircraft accident reports, international runway surface regulation, and aircraft braking performance regulation, it was concluded that significant improvement in the management of runway surface characteristics can be achieved. Areas for potential improvement in the current systems for aircraft skid resistance include gaps in the operational reporting of prevailing runway contamination, as well as friction and surface texture measurement and interpretation protocols. Furthermore, aircraft braking performance regulations are not related to actual runway surface friction levels, resulting in reportedly good runways being found to provide inadequate aircraft skid resistance in certain conditions. Recommendations include improvements in the management of runway friction and texture measurement and analysis during pavement design, and through the service life of the pavement surfaces. Finally, the basis of an improved international runway surface engineering design and management system is outlined. Recommendations can reduce the risk of aircraft skidding accidents in the future.